Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd004135.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Microwave thermotherapy for benign prostatic hyperplasia

Abstract: Microwave thermotherapy techniques are effective alternatives to TURP and alpha-blockers for treating symptomatic BPH for men with no history of urinary retention or previous prostate procedures and prostate volumes between 30 to 100 mL. However, TURP provided greater symptom score and urinary flow improvements and reduced the need for subsequent BPH treatments compared to TUMT. Small sample sizes and differences in study design limit comparison between devices with different designs and energy levels. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 54 publications
0
20
0
2
Order By: Relevance
“…This has mostly been driven by a decrease in thermotherapy. TUNA and TUMT have been traditionally viewed as lacking the long term therapeutic efficacy of TURP 7,9,18 . This decrease in rate of thermotherapy coincides with the increase in the utilization of laser vaporization.…”
Section: Resultsmentioning
confidence: 99%
“…This has mostly been driven by a decrease in thermotherapy. TUNA and TUMT have been traditionally viewed as lacking the long term therapeutic efficacy of TURP 7,9,18 . This decrease in rate of thermotherapy coincides with the increase in the utilization of laser vaporization.…”
Section: Resultsmentioning
confidence: 99%
“…We could not examine trends in the use of transurethral microwave thermotherapy (TUMT) and transurethral needle ablation (TUNA) of the prostate, because the SASD and SID databases do not reliably capture these office based procedures. 6 However, TUMT and TUNA offer less durable results, 21,22 so a clinical decision for a patient with symptomatic LUTS first involves the decision for an operative versus office based procedure and then secondarily a decision for or against laser prostatectomy. Therefore, a comparison of laser prostatectomy and TURP more accurately reflects the real clinical decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…35 Although associated with increased catheterisation time and urinary retention rate compared with TURP, TUMT had significantly lower hospitalisation time and rates of clot retention, blood transfusion, TUR syndrome and sexual dysfunction. 34 Twelve-month retreatment rates were significantly higher for TUMT (7.5%) than TURP (1.1%).…”
Section: Transurethral Microwave Therapymentioning
confidence: 86%
“…A Cochrane systematic review of TUMT found it improved the symptom score (65%) and Q max (70%) although this was inferior to TURP. 34 Initially, it was thought that urinary retention was a contraindication to TUMT due to post-procedure prostatic oedema; however, some success has been reported in the setting of retention. 35 Although associated with increased catheterisation time and urinary retention rate compared with TURP, TUMT had significantly lower hospitalisation time and rates of clot retention, blood transfusion, TUR syndrome and sexual dysfunction.…”
Section: Transurethral Microwave Therapymentioning
confidence: 99%